2009
DOI: 10.15365/cate.2142009
|View full text |Cite
|
Sign up to set email alerts
|

Can green roofs provide habitat for urban beeds (Hymenoptera: Apidae)?

Abstract: Increasing urbanization of many regions of the world has resulted in the decline of suitable habitat for wild flora and fauna. Green roofs have been suggested as a potential avenue to provide patches of good-quality habitat in highly developed regions. In this study, we surveyed green roofs for bee diversity and abundance to determine their potential as quality habitats in an urban area for these important pollinators. By comparing various biodiversity measures between green roofs and ground-level sites, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 30 publications
6
63
0
Order By: Relevance
“…This was also revealed in our study, because fine substrates as well as substrate depth, affected the diversity of ground nesting wild bees on green roofs. Like in other studies (Brenneisen 2005;Colla et al 2009;Tonietto et al 2011), we found Lasioglossum and Halictus species in high abundance (340 individuals) and species richness (20 species) compared to Andrena species with only few or single individuals per species. Two explanations seem reasonable for this observation: Firstly, Andrena species occurrence is more scattered because the females breed solitary.…”
Section: Wild Bee Traitssupporting
confidence: 87%
See 3 more Smart Citations
“…This was also revealed in our study, because fine substrates as well as substrate depth, affected the diversity of ground nesting wild bees on green roofs. Like in other studies (Brenneisen 2005;Colla et al 2009;Tonietto et al 2011), we found Lasioglossum and Halictus species in high abundance (340 individuals) and species richness (20 species) compared to Andrena species with only few or single individuals per species. Two explanations seem reasonable for this observation: Firstly, Andrena species occurrence is more scattered because the females breed solitary.…”
Section: Wild Bee Traitssupporting
confidence: 87%
“…Similar wild bee communities have been reported on green roofs and ground level habitats in Toronto (Colla et al 2009) and Chicago (Tonietto et al 2011) but higher wild bee diversity on ground sites was related to higher entomophilous plant diversity. The habitat quality of green roofs for wild bees was highlighted by observations of locally and/or nationally rare species (Kadas 2006) and of wild bee species newly recorded on green roofs (Ksiazek et al 2014;MacIvor et al 2014).…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, there is also a tendency, through international use of the same few preferred plant species in construction of green roofs (and green walls), to broadly homogenise these areas as 'global habitats'. Such areas have attracted attention as resources suitable for urban bees and honey production (Colla et al 2009 ) but, more widely, are viewed as having considerable benefi ts for urban wildlife conservation. Potential for extending the principle is enormous: Kadas ( 2006 ) recapitulated Jones' ( 2002 ) estimate that Greater London contains 24-26,000 ha of roof space, for example.…”
Section: Novel Habitats: Green Roofs and Green Wallsmentioning
confidence: 99%